Waltércio Caldas: a arte que tece o ar - Flores, Cristine Monteiro (1998)
The subject of this essay focus, primarily, on the contemporary world seen through the art object, by the subjective response of the artist to it. In a world where the technological achievements engender a vertiginous time to our quotidian life, while spaces become wide in range though qualitatively exiguous, we bring about an art which deals with the search for space quality according to our interior tempos. This point might sound like nonsense in the understanding of this very contemporary world we are engaged on getting to grips with. On the contrary, the art of Waltércio Caldas will reveal, through his approach, its connection with this contemporary reality, where it is inserted, while emboding and discussing its complexity. Yet, evoking, at the same time, the particular and expressive poetry the universe of the current man distills. Waltércio Caldas has been considered one of the most important artists in the Brazilian art world. His approach handles various media starting off with drawings towards the object, enlarging its scale till finally reaching the public spaces. In investigating this passage we do not mean to deal with an ambitious number of pieces and questions. The study of Waltércio Caldas’ art will lead, at the end, to one unique proposition: a coherent oeuvre of a singular artist who speaks a universal language, the one of a man in search of himself.